Partisipasi Petani Dalam Kegiatan Pengembangan Kawasan Manggis di Kota Sawahlunto - Sari, Wulan; Syarfi, Ira Wahyuni; Khairati, Rusda (Syntax Literate, 2025)
This study aims to determine the level of farmer participation and the factors influencing farmer participation in mango area development activities. This research uses a quantitative approach with a survey method. The location was chosen purposively. The sampling technique was carried out using simple random sampling, with a sample of 55 farmers involved in mango area development activities. Data analysis was conducted using descriptive statistics and SEM analysis through the Partial Least Square (PLS) approach. The results of the study indicate that farmer participation in the planning and implementation stages is in the high category, while the evaluation stage is in the medium category. The factors that significantly influence farmer participation in mango area development activities are farmer characteristics, opportunities, abilities, willingness, and the role of extension officers.